Growth and development of narbon vetch (Vicia narbonensis L.) genotypes in the semi-arid central Turkey - Fırıncıoğlu, H. K.; Unal, S.; Pank, Z.; Beniwal, S. P. S. (Spanish Journal of Agricultural Research, 2012)
In order to investigate the growth and yield potential of narbon vetch (Vicia narbonensis L.), to elucidate the possible associations of plant traits, to inquire the basics of responses shown by genotypes across years through examining of genotype × year interaction effect, and to extrapolate the nature of adaptation, 27 accessions were evaluated for yield and yield related characters over four subsequent cropping seasons (1994-98) in the central Turkey. Days to harvest, biomass, seed yield, and harvest index were measured, and the results were analyzed by multiple statistical procedures: principal component analysis, linear regression analysis, cluster analysis, descriptive statistics, analysis of variance and additive and multiplicative model analysis. Four year effects were grouped into three classes (good, fairly-good and poor). Seed yield was positively correlated with days to harvest in the first (p<0.05) and fourth (p<0.001) years, and with biomass in all years, which made them plastic and fixed traits respectively. For seed yield, the 27 genotypes were separated into four groups, and year and interaction effects were found to be highly significant (p<0.001). Certain genotypes behaved differently; G25 and G11 were more suitable for specific adaptation, while G2, G4, G6 and G27 were best for broad adaptation. These selected genotypes could be used as a set of reference lines in the evaluation of narbon vetch germplasm for better yield and adaptation. The enhanced developmental flexibility through adjusting plant growth-longevity combined well with higher biomass and harvest index is the primary form of narbon vetch adaptation to the semi-arid central Turkey and similar environments in the Mediterranean area.